Educational Service Quality in Postgraduate Distance Education: Evidence from Indonesia - Siti Julaeha; Kristanti Ambar Puspitasari; Maya Puspitasari (Yayasan Nurul Yakin Bunga Tanjung, 2026)
The post-pandemic expansion of digital learning has intensified competition among open and distance learning (ODL) institutions, making educational service quality essential for enhancing student learning experiences. Despite extensive research on service quality in higher education, limited evidence explains how postgraduate students prioritise service improvements in blended ODL environments. This study identifies the educational service attributes that postgraduate students consider most important, evaluates institutional performance, and prioritises improvement areas at Universitas Terbuka (UT), Indonesia. A cross-sectional survey of 345 postgraduate students assessed 78 indicators across the five SERVQUAL dimensions. Data were analysed using descriptive statistics, importance performance gap analysis, and Importance Performance Analysis (IPA). Results showed that perceived performance (M = 3.59) consistently fell below importance (M = 3.75), indicating unmet student expectations. Responsiveness exhibited the largest performance gap (0.26), while eight attributes, primarily related to tutor and administrative responsiveness, were identified as priorities for improvement. The largest gaps were found in the timeliness of grading and feedback, demonstrating that IPA quadrants alone may overlook critical service priorities. By combining IPA with ranked gap analysis, this study offers a more robust approach to prioritising service improvements and provides practical guidance for enhancing educational service quality and student learning experiences in postgraduate distance education.